ASMA E FATORES DE RISCO ASSOCIADOS EM ADOLESCENTES DE 13 E 14 ANOS DE IDADE DA CIDADE DE SÃO LUÍS, MARANHÃO - Lima, Willy Leite (2009)
INTRODUCTION: Asthma is one of the most common chronic diseases among youngsters. There are only a few studies of its prevalence in Brazil. OBJECTIVE: Estimate the prevalence of asthma and its associated risk factors on students around the age of 13 and 14 in the city of São Luís MA. METHODS: Transversal study using International Study of Asthma and Allergies in Childhood (ISAAC) methodology in adolescents from São Luís (MA) who were selected by random sampling. Data were collected from July/2008 until May/2009 and a standardized Phase1 - ISAAC questionnaire was used as well as a complementary questionnaire. RESULTS: The research involved 3.069 adolescents in which 1.136 (37%) were male and 1.933 (63%) were female. 12,7%, of the prevalence of asthma presented no statistically meaningful difference between gender. The related symptoms to asthma presented the following prevalence: 32,4% of wheezing at some point in life, 12,5% of wheezing at least once in the last 12 months, 8,47% of troubled sleep because of the wheezing; 3,91% of speech difficulties because of the wheezing; 9,84% of wheezing after physical exercises and 27% of nocturnal dry cough. The latter was only significantly noticed on girls. The risk factors associated to asthma that had any statistical meaning were: family history of asthma (RP=2,72; IC95%=2,08-3,56), respiratory infections in the beginning of life (RP=1,78; IC95%=1,33-2,39), eczema (RP=1,65; IC95%=1,31-2,09), passive smoking (RP=1,41; IC95%=1,11-1,79), wheezing in the beginning of life (RP=2,79; IC95%=2,08- 3,73) and allergic rhinitis (RP=2,43; IC95%=1,90-3,11). CONCLUSION: The study sample in São Luis shows a prevalence of asthma of 12,7%, being within the global average and inferior to the Brazilian average, without any gender predominance. The female prevalence of the asthma symptoms between gender was noteworthy only towards the nocturnal dry cough. The associated risk factors found were asthma family history, respiratory infections in the beginning of life, atopic eczema, passive smoking, wheezing in the beginning of life and allergic rhinitis.